Review on Biochemical Composition and Micro-flora of Prawns - Ginson, J.; Bindu, J. (Fishery Technology, 2017)
Prawns are highly demanded seafood commodity both in domestic and International markets due to their nutritional value and unique taste. However, its trading is a risky business due to quick perishable nature and the formation of black spots on the exoskeleton. Biochemical composition such as water activity, pH and autolytic enzymes of the prawn significantly influence the degree of spoilage; moreover, prawns are scavengers and filter feeders which cause them to accumulate several bacteria in their body, which also accelerates the spoilage process. Hence, basic information regarding the biochemical composition and micro-flora of prawn are highly relevant to find out suitable preservation techniques and the production of various value added products. This article reviews the available information on the moisture, sarcoplasmic protein, myofibrillar proteins, stroma protein, non-protein nitrogen (NPN), free amino acid, saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids (PUFA), mineral content and microflora of the prawns.